Rare earth elements (REE) as geochemical clues to reconstruct hydrocarbon generation history - Ramirez-Caro, Daniel (Kansas State University, 2013)
The REE distribution patterns and total concentrations of the organic matter of the Woodford shale reveal a potential avenue to investigate hydrocarbon maturation processes in a source rock. Ten samples of the organic matter fraction and 10 samples of the silicate-carbonate fraction of the Woodford shale from north central Oklahoma were analyzed by methods developed at KSU. Thirteen oil samples from Woodford Devonian oil and Mississippian oil samples were analyzed for REE also. REE concentration levels in an average shale range from 170 ppm to 185 ppm, and concentration levels in modern day plants occur in the ppb levels. The REE concentrations in the organic matter of the Woodford Shale samples analyzed ranged from 300 to 800 ppm. The high concentrations of the REEs in the Woodford Shale, as compared to the modern-day plants, are reflections of the transformations of buried Woodford Shale organic materials in post-depositional environmental conditions with potential contributions of exchanges of REE coming from associated sediments. The distribution patterns of REEs in the organic materials normalized to PAAS (post-Archean Australian Shale) had the following significant features: (1) all but two out of the ten samples had a La-Lu trend with HREE enrichment in general, (2) all but two samples showed Ho and Tm positive enrichments, (3) only one sample had positive Eu anomalies, (4) three samples had Ce negative anomalies, although one was with a positive Ce anomaly, (5) all but three out of ten had MREE enrichment by varied degrees. It is hypothesized that Ho and Tm positive anomalies in the organic materials of the Woodford Shale are reflections of enzymic influence related to the plant physiology. Similar arguments may be made for the Eu and the Ce anomalies in the Woodford Shale organic materials. The varied MREE enrichments are likely to have been related to some phosphate mineralization events, as the Woodford Shale is well known for having abundant presence of phosphate nodules. The trend of HREE enrichment in general for the Woodford Shale organic materials can be related to inheritance from sources with REE-complexes stabilized by interaction between the metals and carbonate ligands or carboxylate ligands or both. Therefore, a reasonable suggestion about the history of the REEs in the organic materials would be that both source and burial transformation effects of the deposited organic materials in association with the inorganic constituents had an influence on the general trend and the specific trends in the distribution patterns of the REEs. This study provides a valuable insight into the understandings of the REE landscapes in the organic fraction of the Woodford Shale in northern Oklahoma, linking these understandings to the REE analysis of an oil generated from the same source bed and comparing it to oil produced from younger Mississippian oil. The information gathered from this study may ultimately prove useful to trace the chemical history of oils generated from the Woodford Shale source beds.
Keywords: Woodford Shale; Rare Earth Elements; Anadarko Basin; Petroleum System; Geochemistry; Energy (0791); Geochemistry (0996); Geology (0372)